2000
DOI: 10.1017/s0012162200000190
|View full text |Cite
|
Sign up to set email alerts
|

Children with neurological disorders do not always need fundoplication concomitant with percutaneous endoscopic gastrostomy

Abstract: Whether antireflux surgery should be routinely performed at the time of gastrostomy in children with neurological disorders is debatable because of the risk of gastroesophageal reflux. Some argue that these children should be screened for occult gastroesophageal reflux as this will determine the need for fundoplication. This study retrospectively examines outcome in 29 children with neurological disorders who underwent percutaneous endoscopic gastrostomy (PEG) without concomitant fundoplication. Children were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…over-granulation, irritation and tenderness), which were easily managed. Similar to other studies, anti-reflux techniques were required after PEG in several cases (Sulaeman et al, 1998;Puntis et al, 2000). The mortality rate was similar to that reported previously (Avitsland et al, 2006) and it was found to be related to the underlying disease, and not to the nutritional support itself.…”
Section: Discussionsupporting
confidence: 85%
“…over-granulation, irritation and tenderness), which were easily managed. Similar to other studies, anti-reflux techniques were required after PEG in several cases (Sulaeman et al, 1998;Puntis et al, 2000). The mortality rate was similar to that reported previously (Avitsland et al, 2006) and it was found to be related to the underlying disease, and not to the nutritional support itself.…”
Section: Discussionsupporting
confidence: 85%
“…It is known that the frequency of GER is increased in patients with neurological diseases (14). Some studies have supported the view that the severity of GER increases after PEG in these patients and some others have reported the opposite (15)(16)(17). However, Puntis et al (17) recommended that simultaneous antireflux operation should not be performed in these patients and investigations for GER should be avoided in patients without complaints.…”
Section: Discussionmentioning
confidence: 99%
“…53 In response to earlier suggestions for "the need for a 'protective' antireflux operation in children referred for feeding gastrostomy," 54 Puntis et al provided data "in the child with neurological disabilities without symptoms indicating severe gastroesophageal reflux" and their conclusions that "fundoplication is unlikely to be necessary as a consequence of percutaneous endoscopic gastrostomy" and that the number of antireflux surgical procedures should be reduced. 55 Similarly, the outcome reports of variations in fundoplication techniques (eg, open, laparoscopic) offer differences in respective advantages and disadvantages. 56,57 A number of complications and adverse effects have been described and attributed to fundoplication surgery: alterations in gastric tone (perhaps related to injury of the vagal nerve at operation); accelerated gastric emptying ("dumping syndrome"); delayed gastric emptying after surgery related to vagal nerve injury; and retching (potentially related to visceral afferent sensitivity and vagal nerve injury).…”
Section: Fundoplication Surgerymentioning
confidence: 99%